If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-42=(-3/4)(f-4)
We move all terms to the left:
-42-((-3/4)(f-4))=0
Domain of the equation: 4)(f-4))!=0We multiply parentheses ..
f∈R
-((-3f^2-3/4*-4))-42=0
We multiply all the terms by the denominator
-((-3f^2-3-42*4*-4))=0
We calculate terms in parentheses: -((-3f^2-3-42*4*-4)), so:We get rid of parentheses
(-3f^2-3-42*4*-4)
We get rid of parentheses
-3f^2-3-4-42*4*
We add all the numbers together, and all the variables
-3f^2
Back to the equation:
-(-3f^2)
3f^2=0
a = 3; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·3·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:$f=\frac{-b}{2a}=\frac{0}{6}=0$
| (35+y)-(35-y)=60-10 | | –3x+18=–3x+ | | x+20=2x+1 | | 0.2(x-3)+0.25=-1 | | (X)2-15x+56=0 | | |6z+3|=7 | | 0.2(x-3)+0.25=1 | | 24(c-66)=22,800 | | 3z/7+3=5 | | 15w=16+7w | | 23=3-2u | | 6w-4=50 | | 7(y-9)=-7 | | 7=w/9+4 | | (2/ 15+y)−7 /30=1 /10 | | 28x+8=52 | | 6=2w+41=3w | | -187-12x=9x+65 | | g+71/4=101/2 | | -39-4x=11-2x | | -32y^2+72y+0=0 | | 8x-99=171-2x | | 7x-x-6x=8 | | C-4=3c+9 | | Z-3z=9z-1-1z | | 101/2t=21/8 | | 10h+h-6h=5 | | 64+(4(3x+2))=180 | | Y=41-x/2 | | 3^2+x-7=4x | | f-3.8=9.2 | | a÷4+3=14 |